2021
DOI: 10.29333/iji.2021.14428a
|View full text |Cite
|
Sign up to set email alerts
|

A Regression Analysis Approach to Measuring the Influence of Student Characteristics on Language Learning Strategies

Abstract: Mapping multivariate influence of learner characteristics on behavior highlights models in learning. To this end, we explored the relationships between strategies and learning characteristics and used regression analysis to understand how learner characteristics predict learning strategy choices. A cross-sectional research design with 175 students revealed high levels of strategy use, with statistically significant correlations within and between Strategy Inventory for Language Learning (SILL; Oxford, 1990) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…SILL has been widely used for years and is well-recognized as a high-standard instrument to examine foreign/second language learners' LLS use. Its validity and reliability have been endorsed by many studies (Almusharraf & Bailey, 2021;Damanik, 2022). These studies revealed that, when employing Cronbach's alpha, SILL's general reliability is above .9, even when translated into other languages.…”
Section: Research Instrumentmentioning
confidence: 95%
See 3 more Smart Citations
“…SILL has been widely used for years and is well-recognized as a high-standard instrument to examine foreign/second language learners' LLS use. Its validity and reliability have been endorsed by many studies (Almusharraf & Bailey, 2021;Damanik, 2022). These studies revealed that, when employing Cronbach's alpha, SILL's general reliability is above .9, even when translated into other languages.…”
Section: Research Instrumentmentioning
confidence: 95%
“…As Oxford (2003) stated, LLS is a vital factor that helps figure out how and how well a foreign language is learned. For years, LLSs have been explored by many researchers (Almusharraf & Bailey, 2021;Damanik, 2022;Oxford, 1990Oxford, , 2003. However, as Jaekel (2020) stated, the concept of LLSs has not been defined uniformly.…”
Section: Literature Review Language Learning Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Boys who reported higher scores on deep learning showed more deep learning strategies, whereas this was not true for girls (Umapathy et al, 2020). Almusharraf mentioned compensation strategies in his learning strategy research, he pointed out that compensation strategies involved switch language, adjust message, and mobilize relevant knowledge (Almusharraf & Bailey, 2021). Male and female learners differ greatly in the use of “compensation strategies.” Undergraduates' gender indicate a significant difference in “compensation” component, the concept of compensation strategy.…”
mentioning
confidence: 99%